Analisis Pengaruh Biaya Operasional Pendapatan Operasional (BOPO) dan Non Performing Financing (NPF) Terhadap Profitabilitas Bank Syariah - Edy Junaedi (STAI Asy-Syukriyyah, 2016)
Sharia Bank is well-known as a bank which is resistant to the global crisis that hitted Indonesia couple years ago. The performance of Sharia Bank could be maintained so that continuity of bussines also could be well maintained. Those performance could be measured by the size of the Sharia banking profitability. The factors affecting the profitability of Islamic banks used in this study are BOPO NPF and ROA. While the purpose of this study was to determine the effect of BOPO and NPF toward the profitability of Sharia banks. The population used for the study are all of sharia banks Bank Umum Sariah (BUS) and Unit Usaha Syariah (UUS) in Indonesia have been published by Otoritas Jasa Keuangan (OJK) from 2015 to 2016. The data of this study used secondary data from the website of Otoritas Jasa Keuangan. The method of data analysis which was used is multiple linear regression analysis. The results of this study indicate that the BOPO variabel has significant effect on ROA and NPF variable has no significant effect on ROA in Sharia Banking Industry. While BOPOand NPF variabel had significant influence with negatif direction.